2019
DOI: 10.1108/ijlls-06-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of lesson study through the views of Lao mathematics teacher educators on the needs, learning and difficulties

Abstract: Purpose The purpose of this paper is to comprehensively explore the current situation of lesson study (LS) implementation and practice among Mathematics Teacher Educators (MTEs) in Teacher Training Colleges (TTCs) across the country in Laos. Moreover, the study investigates MTEs’ professional learning through LS experience, the difficulties they encountered during practicing LS and their urgent needs to deepen their comprehension in the context of LS. Design/methodology/approach Data were collected through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Research on lesson study has also revealed that teachers can jointly develop the teaching and learning process as well as contribute to the development of students' advanced thinking skills, which enables students to gradually develop the learning skills and innovations of the 21st century. In addition, it helps in the design of teaching and learning management, strengthens problem-solving skills in classrooms, and fosters creativity and innovation skills (Inprasitha, 2009;Inthawongsa, 2017;Saosing, 2014;Bayram & Bikmaz, 2018;Shingphachanh, 2020).…”
Section: Souphanouvongmentioning
confidence: 99%
“…Research on lesson study has also revealed that teachers can jointly develop the teaching and learning process as well as contribute to the development of students' advanced thinking skills, which enables students to gradually develop the learning skills and innovations of the 21st century. In addition, it helps in the design of teaching and learning management, strengthens problem-solving skills in classrooms, and fosters creativity and innovation skills (Inprasitha, 2009;Inthawongsa, 2017;Saosing, 2014;Bayram & Bikmaz, 2018;Shingphachanh, 2020).…”
Section: Souphanouvongmentioning
confidence: 99%
“…Eksperimen pengajaran Penilaian Rangka kerja Aplikasi teknologi (Horn et al, 2017;Jesus et al, 2020;Lindenskov & Lindhardt, 2019;Little, 2020;Nicol et al, 2020;Shirrell et al, 2018;Wilkie, 2017) Kumpulan Lesson study (Cavanagh & Mcmaster, 2017;Chua, 2019;Jiang et al, 2019;Mhakure, 2019;Richit & Tomkelski, 2020;Shingphachanh, 2019;Soto et al, 2019;Stokes et al, 2019) Perbincangan/perkongsian dalam komuniti Refleksi Amalan Prestasi pelajar (Alles et al, 2019;Brodie & Chimhande, 2020;Chauraya & Brodie, 2017, 2018Kim, 2021;Kim & Heaton, 2019;Mohan & Chand, 2019;Patahuddin et al, 2020) www.msocialsciences.com…”
Section: Kumpulan Penyelidikanunclassified
“…In addition, it helps in the design of teaching and learning management, strengthens problem-solving skills in classrooms, and fosters creativity and innovation skills. (Inprasitha, 2009;Inthawongsa, 2017;Saosing, 2014;Bayram & Bikmaz, 2018;and Shingphachanh, 2020).…”
Section: Introductionmentioning
confidence: 99%